Detection of Genotipically Related Multi-resistant Escherichia coli Isolates in Pig Feces and Carcasses - Pissetti, Caroline; Werlang, Gabriela Orosco; Kich, Jalusa Deon; Cardoso, Marisa (Acta Scientiae Veterinariae, 2016)
Background: Antimicrobial resistant bacteria are considered a hazard not only for the treatment of animal diseases but also for public health. Commensal bacteria, such as Escherichia coli are considered a good indicator of antimicrobial resistance in the population, because it is a gut inhabitant and thus undergoes constant pressure of selection by the administration of antimicrobials. Regarding the public health, it is important to evaluate if resistant bacteria carried in the intestinal content of slaughter pigs can be found on the surface of pre chill carcasses. Therefore, the aims of this study were to evaluate the frequency of antimicrobial resistance in E. coli isolated from feces and pig carcasses; and to assess if multi-resistant isolates from both sources were phenotypically and genotypically related. Materials, Methods & Results: Two sampling cycles were conducted in three pig slaughterhouses (A, B and C). In each cycle, samples were collected form: i. feces deposited on the pen floor of the lairage; ii. surface of carcasses at the prechill step. Samples were submitted to a protocol of isolation and confirmation of Escherichia coli. Isolates were grouped according to the origin: feces (n = 355); carcasses (n = 319); and evaluated for antimicrobial resistance by agar diffusion test. Ninety two isolates presenting multidrug resistance profile were analyzed by pulsed-field gel eletrophoresis (PFGE). Among the 674 isolates of E. coli, 7.4% were susceptible to all tested antibiotics while 79.5% (536/674) were multi-resistant. The most frequent resistance patterns were displayed to tetracycline (Tet, 85.9%), ampicillin (Amp, 73.0%), sulfonamide (Sul, 70.0%), florfenicol (Flo, 65.0%) and nalidixic acid (Nal, 58.9%). The most frequent multi-resistance profile among isolates from both origins was [AmpFloNalSulTet]. Multiresistant isolates originated from feces and carcasses displaying genotypically related pulsotypes (≥70% similarity) were found in all three slaughterhouses. Discussion: In agreement with other studies, E. coli isolated from pig feces and carcasses demonstrated a high frequency of antimicrobial resistance and multi-resistance. The most frequent resistance profiles included antimicrobials frequently used on farm as well as drugs that have been banned as feed additives some years ago in Brazil. The selection of resistant strains may be related to the selection pressiondue to the use of antimicrobials in the pig production chain as well as the co-selection of resistance mediated by genes located in common genetic elements. Therefore, the ban of an individual drug is not always associated with the immediate disappearance of the resistance phenotype in the bacteria population. The fact that most multi-resistant E. coli isolates from carcasses belonged to pulsotypes related to those originated from feces samples indicates that resistant E. coli isolates selected on farm may be able to survive the slaughter process and be found on the carcass. In this case, the possibility of those strains being able to reach the population through the consumption of pork products may have to be considered. This hazard has motivated the ban of antimicrobial use in animals in some countries. However, the ban of antimicrobials use on farm is a controversial issue, due to the economical losses that may result from this measure. Therefore, the prudent use of antimicrobials on farm should be encouraged and its influence in the multi-resistance profile of the enteric microbiota should be further studied.